Pemilhan Pemasok Bahan Baku Kayu Handle Raket Dengan Menggunakan Metode Fuzzy Analitycal Hierarchy Process - Pangestu, Yofa (Jurnal Teknik Industri, 2015)
Eternal racket company located in the Klayatan is a company engaged in manufacturing, where output is produced in the form of sports equipment. Given these problems, the Company is required Eternal racket must evaluate suppliers and choose which supplier should be selected with a view limits the capacity and various characteristics of suppliers. For that decision-making in the selection of suppliers is very important. Based on this problem researchers try to provide alternative solutions to the problem of decision-making by integrating the F-AHP is the combination of AHP technique to approach the concept of fuzzy logic. Although AHP is used in dealing with qualitative and quantitative criteria in MCDM but fuzzy AHP is considered better in describing vague decision of the AHP. and the supplier is a supplier selected priority A (P_A) with highest weight is 0.389.